Developing India's Corporate Bond Market - World Bank (Washington, DC, 2014)
A well-developed corporate bond market is essential for the efficiency and stability of a country's financial system and the overall growth of its economy. Issuers and investors' access to the market provides for financial diversification and facilitates necessary financing, which benefits not only AAA-rated corporations but also less well known, sub-investment grade corporations and infrastructure developers. This note examines the state of India's corporate bond market, identifies constraints that inhibit its size and depth, and suggests reform measures that India needs to take to develop its market into a competitive source of financing for a wide range of issuers and an attractive investment for a wide range of investors. Recommendations are based not only on an assessment of conditions in India, but also on relevant international experience.